DIGITAL TRANSFORMATION OF EXPORT-ORIENTED ECONOMY OF RUSSIA - P. Tereliansky (Вестник университета, 2019)
The subject of the study of this article are the statistics on the volume of sales of four hundred leading Russian companies, consolidated by media holdings «Expert» and «RosBusinessConsulting». The process of transformation of the export-oriented economy of Russia into a digital economy is proposed to indirectly assess the volume of sales of leading domestic companies. The author supposes, that the increase in the share of sales of IT-oriented industries in the total volume of leading domestic companies reflect the process of digitalization of the economy. The results of the study show that 31,8 % of the total sales of the 10 largest companies in Russia can be attributed to the digital economy, which allows us to declare a steady movement towards the transformation of the economy, which is based on the processes associated with the creation, transformation, transfer and storage of intangible digital entities.